PENDAMPINGAN STRATEGI JEJARING USAHA DALAM MENDORONG KEMANDIRIAN EKONOMI PEREMPUAN ‘AISYIYAH KOTA PAREPARE - Usman, Usman; Ruslang T, Ruslang T; Sudirman, Sudirman; Rahman, Abdul (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Business networking strategy mentoring for participants of the 'Aisyiyah Entrepreneurship School in Parepare City was conducted in response to the low utilization of business networks by female MSMEs, who have so far relied on limited relationships and have not optimized collaboration and digital networks. This activity aims to improve understanding and practical skills in building and mapping networks according to business needs. The mentoring was carried out through a participatory approach on November 1, 2025, at the 'Aisyiyah Multipurpose Building in Parepare City. The results of the activity showed a significant increase in participants' understanding of the benefits of networking, potential strategic partners, and the use of digital networks, in line with research findings from the past five years that emphasize the importance of networking in women's empowerment. Participants also demonstrated higher motivation to expand their business networks and begin planning community-based and digital collaborations. Thus, this activity was effective in strengthening participants' capacity to build targeted business networks, which ultimately supports the economic independence of 'Aisyiyah women and the aspirations of entrepreneurs in Parepare City.